World review of the genus Strongylophthalmyia Heller (Diptera: Strongylophthalmyiidae). Part I: Introduction, morphology, species groups, and review of the Strongylophthalmyia punctata subgroup - Evenhuis, Neal L. (Zootaxa, 2016)
The Strongylophthalmyia punctata subgroup, comprising 24 species with armored fore femora, and restricted primarily to SE Asia, is reviewed. Eighteen new species, S. albisternum, n. sp. (Thailand), S. borneensis, n. sp. (Borneo), S. caestus, n. sp. (Philippines), S. darlingi, n. sp. (Sumatra), S. federeri, n. sp. (Philippines), S. hauseri, n. sp. (Thailand, Vietnam), S. indochinensis, n. sp. (Cambodia, Thailand, Vietnam), S. inundans, n. sp. (Philippines), S. laosensis, n. sp. (Laos), S. lowi, n. sp. (Peninsular Malaysia), S. malayensis, n. sp. (Peninsular Malaysia), S. nigripalpis, n. sp. (Peninsular Malaysia), S. oxybeles, n. sp. (Sumatra), S. pappi, n. sp. (Thailand), S. phillindablank, n. sp. (China), S. sichuanica, n. sp. (China), S. sumatrana, n. sp. (Sumatra), and S. thailandica, n. sp. (Thailand) are described and illustrated, S. microstyla Shatalkin and S. punctata Hennig are redescribed based on examination of the holotypes, and a key to species of the subgroup is presented. A general taxonomic overview of the genus Strongylophthalmyia is given with discussion of and keys to proposed species groups.